Eco-cultural perspectives on plant diversity and NDVI in mountain pastures: a comparative study of Finail Valley (Italy) and Vercenik Valley (Turkey) - Basar, Oguz Kemal; Ugurlu, Emin; Wellstein, Camilla (Frontiers Media Sa, 2025)
Transhumance is one of the oldest traditional agricultural practices in Val Senales (Italy) and the Western Pontic Mountains (Turkey), playing a crucial role in shaping alpine ecosystems. This study examines the impact of traditional pastoral management on the distribution of dominant plant species and phytomass levels in summer grazing areas. Grazing routes were analyzed using NDVI values derived from drone-based orthophotos captured at an altitude of 35 m during the peak of the transhumance season in June, allowing for the quantification of vegetation cover and dominant species composition. Ethnographic fieldwork with local shepherds in Finailhof and the Vercenik Valley provided insights into traditional ecological knowledge related to pasture management and seasonal flock movements. Additionally, herbarium methods were employed to identify grazed plant species along the grazing routes. Although both regions share similar alpine climatic conditions, their distinct socio-cultural contexts and land-use histories result in different patterns of grazing impact and phytomass distribution. This bi-disciplinary research examines the relationship between NDVI values, phytomass variation, and dominant plant species in both study sites. The findings highlight the significance of integrating traditional ecological knowledge with remote sensing and ecological field methods to support sustainable pasture management and inform alpine policy frameworks. By combining ecological and ethnographic perspectives, the study contributes to a deeper understanding of the interdependent dynamics between cultural practices and environmental processes in pasture management of high-mountain landscapes.
Keywords: transhumance; alpine farming; NDVI; ethnography; grazing